An Update to the Pilot Study of 177Lu-PSMA in Low Volume Hormone-Sensitive Prostate Cancer - Privé, Bastiaan M.; Muselaers, Constantijn H. J.; van Oort, Inge M.; Janssen, Marcel J. R.; Peters, Steffie M. B.; van Gemert, Willemijn A. M.; Uijen, Maike J. M.; Schilham, Melline M. G.; Sedelaar, J. P. Michiel; Westdorp, Harm; Mehra, Niven; Gotthardt, Martin; et al. (Frontiers in Nuclear Medicine, 2022)
Abstract: 177Lu-PSMA-617 radioligand therapy is a novel treatment for end-stage prostate cancer which could also be applied to patients with hormone sensitive prostate cancer with high expression levels of prostate-specific membrane antigen (PSMA). In this perspective, we review the recent results of toxicity, radiation doses, and treatment effect of 177Lu-PSMA in low volume metastatic hormone sensitive prostate cancer patients. Moreover, we present long-term follow-up data such as toxicity and time without androgen deprivation therapy of the patients that participated in this trial. All in all, 177Lu-PSMA appeared to be a feasible and safe treatment modality in this setting, also at long-term follow-up. We observed that especially men with a prostate-specific antigen (PSA) response of more than 50% seemed to benefit from this therapy by postponing androgen deprivation therapy and thus preserving the quality of life.